AN ANALYSIS OF THE IMPACT OF AN INTERDISCIPLINARY PROJECT ASSIGNMENT ON STUDENTS’ LEARNING OUTCOMES - Bessie Ong; Kok Choy Cheong, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper presents the design and analysis of an interdisciplinary experiential learning project to simulate a food manufacturing workplace experience within the course curriculum. The objectives are for students to accomplish various learning outcomes, along with the understanding of professional implications. Using a specific food of choice, small teams collaborated to cook a healthier version of that food for sale at a profit. Evaluation of learning outcomes through the lens of Fink’s taxonomy is exploratory and qualitative. At the end of this project, students are able to achieve learning outcomes mainly in the areas of knowledge application, human dimension and integration, and to a lesser extent in the other domains. The project benefits students in a second division course when they are yet ready for industrial internship by providing a hands-on insight on what to expect in their working lives.